Efektivitas Lembar Kerja Peserta Didik (LKPD) Terhadap Pemahaman Proses Penanaman Edamame pada Siswa SMK - Rianto, Muhammad Fajar; Rachmawati, Rivanna Citraning; Wardani, Susilo (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2025)
Edamame cultivation requires a strong technical understanding, such as the arrangement of planting distances, hole depth, and seed treatment, to achieve optimal results. Learning tools, such as student worksheets, are designed to help students systematically understand these technical steps. This study aims to evaluate the effectiveness of student worksheet in improving students' understanding of the edamame planting process at vocational high schools. The study was conducted in November 2024 at SMK Negeri 1 Bawen, class X ATP B. The research employed a descriptive quantitative method with an evaluative approach. Data were collected from the analysis of worksheets completed by 13 student groups, questionnaires completed by 6 students, and field observations. The findings showed that the average worksheet score was 70.8, with 5 groups achieving the "very good" category. The questionnaire data supported these findings, with 5 out of 6 students giving the highest scores to statements indicating that the worksheets helped them independently follow each step of the practical activities. However, some challenges were identified, such as technical difficulties in measuring planting distances and discrepancies between the worksheet instructions and field practices.